Experimental modelling of the hybrid accelerating structure of heavy ion linear accelerator - Bomko, V.O.; Dyachenko, O.F.; Zajtsev, B.V.; Kobets, A.P.; Tishkin, S.S. (Вопросы атомной науки и техники, 2016)
The new prestripping section of the heavy ions linear accelerator with mass-to-charge ratio A/q ≤ 20, allowing to accelerate ions from 6 keV/u to energy of 1 MeV/u is developed. The section represents a combination of diverse accelerating structures in one сavity: with radio frequency quadrupole focusing (RFQ) and structure with drift tubes (DTL). In contrast to conventional acceleration systems, the use of the more compact hybrid сavity simplifies system operation due to their coupled complex acceleration electrode and integrated peripheral devices, such as their power and vacuum systems. However thus distribution RF-field in such structure and its frequency characteristics essentially changes. It is shown that using tuning devices: tuners, end resonant, inductive and capacitive elements in such structure it is possible to provide require frequency and uniform distribution of electric field in an accelerating path of the hybrid сavity. Разработана новая предобдирочная секция ускорителя тяжѐлых ионов с отношением массового числа к зарядовому A/q ≤ 20, позволяющая ускорять ионы от 6 кэВ/нукл. до энергии 1 МэВ/нукл. Секция представляет собой комбинацию разнородных ускоряющих структур в одном резонаторе: с пространственно-однородной квадрупольной фокусировкой и структурой с трубками дрейфа. В отличие от обычных систем ускорения, использование более компактного гибридного резонатора упрощает систему управления благодаря их связанному комплексу ускоряющих электродов и интегрированных периферийных устройств, таких как системы питания и вакуумная. Однако при этом существенно меняется распределение ВЧ-поля в такой структуре и еѐ частотные характеристики. Показано, что, используя настроечные устройства: тюнеры, концевые резонансные, индуктивно-ѐмкостные элементы, в такой структуре можно обеспечить требуемую частоту и равномерное распределение электрического поля в ускоряющем тракте гибридного резонатора. Розроблено нову передобдіркову секцію прискорювача важких іонів з відношенням масового числа до зарядового A/q ≤ 20, що дозволяє прискорювати іони від 6 кеВ/нукл. до енергії 1 МеВ/нукл. Секція являє собою комбінацію різнорідних прискорюючих структур в одному резонаторі: з просторово-однорідним квадрупольним фокусуванням і структурою з трубками дрейфу. На відміну від звичайних систем прискорення, використання більш компактного гібридного резонатора спрощує систему управління завдяки їх пов’язаному комплексу прискорювальних електродів та інтегрованих периферійних пристроїв, таких як системи живлення й вакуумна. Однак при цьому істотно змінюється розподіл ВЧ-поля в такій структурі та її частотні характеристики. Показано, що, використовуючи настроювальні пристрої: тюнери, кінцеві резонансні, індуктивно-ємнісні елементи, в такій структурі можна забезпечити потрібну частоту та рівномірний розподіл електричного поля в прискорюючому тракті гібридного резонатора.